Factors Causing Early Marriage Of Women In Hinterland Community In Batam City - Tarigan, Renny Adelia; Roza, Nelli; Rosanti , Ayu (Sean Institute, 2022)
Marriage is something to look forward to in human life because through a marriage can form a family that will be continued by having children. The number of cases of early marriage in Indonesia reaches 50 million people with an average marriage age of 19.1 years. The approach used in this study is the f quality approach. This study aims to decrypt the factors causing the rise of early marriage in the Hinterland community. The study involved three married female informants at an early age. The interviews the researchers conducted were four times. The results of this study found factors that cause early marriage of women in hinterland communities, namely low levels of economy, culture, level of education. The results of this research are expected to be used for health workers as eduators and counselors as education to the community along with indigenous leaders about reproductive health in women and the impact of early marriage